2023
DOI: 10.1128/spectrum.02139-21
|View full text |Cite
|
Sign up to set email alerts
|

Sputum Microbiome and Chronic Obstructive Pulmonary Disease in a Rural Ugandan Cohort of Well-Controlled HIV Infection

Abstract: Even with ART available, HIV-infected individuals are at high risk of suffering comorbidities, as shown by the high prevalence of noninfectious lung diseases in the HIV population. Recent studies have suggested a role for the respiratory microbiota in driving chronic lung inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Lavage from adult macaque monkeys also did not appear to contain the phyla Campilobacterota, which was found in lung wash from infant macaque monkeys in our study, but the genus Campylobacter has been reported in the lung of cynomolgus macaque monkeys following infection with Mycobacterium tuberculosis 40 , 42 . Interestingly, Campylobacter in the human lung is associated with inflammatory and immunocompromised conditions such as chronic obstructive pulmonary disease 43 , 44 . It is notable that Campylobacter was only detected in the lung but not oral cavity of animals in our study, suggesting an alternative anatomical route (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Lavage from adult macaque monkeys also did not appear to contain the phyla Campilobacterota, which was found in lung wash from infant macaque monkeys in our study, but the genus Campylobacter has been reported in the lung of cynomolgus macaque monkeys following infection with Mycobacterium tuberculosis 40 , 42 . Interestingly, Campylobacter in the human lung is associated with inflammatory and immunocompromised conditions such as chronic obstructive pulmonary disease 43 , 44 . It is notable that Campylobacter was only detected in the lung but not oral cavity of animals in our study, suggesting an alternative anatomical route (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strict inclusion criteria of this review might influence the clinical outcomes of this study, by leading to a small patient population. Previous studies showed that an absence of Veillonella and an abundance of Staphylococcus was associated with mortality [29,31,32]. Furthermore, it is important to note that most of the included studies relied on conventional culturing methods for pathogen isolation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our systematic search, a focused, non-systematic search from 2015 on microbiome-associated mortality in patients with AECOPD without ICU admission was performed. This search identified an additional four studies on mortality and the microbiome in patients with COPD [14,[29][30][31]. Two studies demonstrated that decreased microbial diversity, the absence of Veillonella, and an abundance of Staphylococcus were associated with increased mortality [29,31].…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…We screened for M.tb infection using QuantiFERON-TB Gold and GeneXpert assays on participants previously enrolled in an existing HIV Lung Microbiome cohort established in rural Uganda. 79 Briefly, the HLM cohort is a longitudinal cohort established in 2018 comprised of 200 individuals stratified by HIV and COPD status. 79 From February 2018 to February 2021, the HLM cohort was randomly recruited from two large independent cohorts, i.e., The Lung Function study in Kampala and Nakaseke (LiNK, comprised of n=656 HIV-negative individuals) and the HIV-infected Lung Function study in Nakaseke (HiLiNK, comprised of n=722 HIV-positive individuals) 26 in the same geographic location.…”
Section: Methodsmentioning
confidence: 99%